ANALISIS PELAYANAN PENGGUNAAN KARTU BPJS KESEHATAN PADA RUMAH SAKIT ISLAM IBNU SINA KOTA PEKANBARU (STUDI KASUS PASIEN RAWAT INAP DAN RAWAT JALAN PADA PENDERITA PENYAKIT DALAM) - Novita Sari; Eka Komalasari (UIR Press, 2018)
Health is a major factor of social prosperity to be realized by the government as public service providers. In this case the government makes a health agencies ie Social Security Implementation Agency for Health Care or Health BPJS. Every Hospital using System BPJS including Islam Ibn Sina Hospital Pekanbaru, which provides health services to the user community cards BPJS one of which is the Disease Patients In either through inpatient or outpatient.The purpose of this study was menganalisisi service card usage BPJS on Islam Ibn Sina Hospital Pekanbaru (Case Study Inpatient and Outpatient On Disease Patients In) and know the constraints that occur in the service process. The researchers took samples in the field of population and registration of 5 people, 2 fields of medical records, BPJS the existing Public Health Hospital 1, the public/patients hospitalized 15 people, community/outpatient 30 people.The technique of sampling for employees Hospital is a sampling pusposive, and for the people who inpatient and outpatient using incidental sampling. While it's a theory that researchers use services Mahmudi is the theory that public service standards consists of 10 indicators, but the researchers took six indicators only in accordance with existing phenomena ie. Simplicity procedures, procedures clarity, certainty of time, completeness of facilities and infrastructure, responsibility and comfort. After all the data is analyzed by qualitative and quantitative methods, the obtained results of the analysis service card usage BPJS at the Islamic Hospital Ibn Sina Pekanbaru (Case Study Inpatient and Outpatient On Disease Patients In) categorized as